IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) DI WILAYAH KECAMATAN RINGINREJO KABUPATEN KEDIRI - Pailan Pailan (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
The existence of the villages in Indonesia recognized by law and they are expressed as a unit of community with specific boundaries. Villages authorized to regulate and manage the affairs of the government, the interests of the local community based community initiatives, the right of the origin and/or customary rights recognized and respected in the administration system of the Republic of Indonesia (Undang-Undang Nomor 6 Tahun 2014 Tentang Peraturan Pelaksanaan Undang-Undang Nomor 6 Tahun 2014 tentang Desa). Based on their jurisprudence, villages in Indonesia have their autonomy rights to maintain their local governance and policy. As a logical consequence of their powers and demands of the implementation of a village is the availability of sufficient funds. The Rural Fund Allocation (ADD) is one of the villages’ funds resource taken from the equalization funds received from the Regency holder Kediri. The practice of the allocation of rural fund allocation (ADD) mostly suffered to its procedure. The most prominent problem within this research is due to missing of the accountability and the lack of the right system that explicitly written in the Technical Direction from the related governance No. 412.6/1843/418.63/2015 about the technical details of the allocation of rural funds year of 2015. This study uses qualitative methodology with the phenomenology and survey approach to reveal and deep understanding of the facts and phenomena related to the research topic. We finally revealed several facts that prove the weaknesses relating to the policy on implementing rural funds (ADD) in villages of Ringinrejo Country, Kediri Regency that directly influences to the transfer process of the rural funds to the villages, weakness on ABPDes accountability and the lack of transparency. Therefore, the fund's accountability in the villages is the natural subject to the money manipulation.